Mendesain Pembangunan Berdasar Perspektif Sosial Budaya - Mudjahirin Thohir (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The development is a deliberate design of cultural change to improve peple’s live.  Change in people knowledge , behavior, or its facilities. However, the people who were  the target of the development,  not necessarily accept it. Why? It is related to how the strategy to bringing together the understanding between  goverment, people, and the development executor.